Coercive paternalism and back-door perfectionism. Issue 5 (13th December 2013) - Pugh, Jonathan
Abstract : In this response piece, I argue that the 'coercive paternalism' that Sarah Conly endorses in her book Against Autonomy veers towards a back-door perfectionism. Although Conly points out that coercive paternalism does not mandate the imposition of alien values upon us in the same way that perfectionism does, I argue that coercive paternalism might yet impose an alien weighting of our own values; this, I suggest, means that coercive paternalism remains perfectionist in spirit, if not in letter. I go on to concede to Conly that coercive paternalism might be warranted in preventing actions that threaten health and that are only carried out on the basis of cognitive error. However, I conclude by claiming that we must take great care about what we presume that people are consuming only on the basis of cognitive error. More specifically, I suggest that it is crucial that we avoid defining our terms in such a manner that it becomes impossible for agents to choose some action that poses a risk to their health without them being accused of making a cognitive error in weighing their values in that way.